Perancangan Standar Operasional Prosedur Dalam Pencatatan Penerimaan dan Pengeluaran Kas Pada TK Islam Al-Khaeriyyah - Muhammad Yaser Alfarisy; Indra Pahala; Ayatulloh Michael Musyaffi (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
Designing a Standard Operating Procedure (SOP) for recording cash receipts and disbursements at Al-Khaeriyyah Islamic Kindergarten as an effort to improve internal control. The research employed a Research and Development (R&D) approach using the ADDIE model. The analysis stage was conducted through interviews, observations, and documentation to identify issues in the cash recording process. The design and development stages produced a draft SOP for cash receipts and disbursements. Implementation was carried out through socialization involving the principal, treasurer, and administrative staff, while the evaluation stage utilized open-ended questionnaires that showed highly positive responses. The results indicate that the SOP serves as an effective guideline for recording cash receipts and disbursements at the school. Future research is recommended to conduct comprehensive implementation and evaluation, as well as further development of the SOP.